KONTRIBUSI PERIODE TABI’IN DALAM PERKEMBANGAN TAFSIR AL-QURAN - Sumarni, Sumarni; Nurudin, Ahmad; Mustofa, Ahmad (Wahana Islamika: Jurnal Studi Keislaman, 2023)
During the Tabi'in era, many figures were well-known as interpreters. They played an important role in developing the science of tafsir and contributed to understanding the Quran. In addition, the Tabi'in figures also provided their views on the social, historical, and linguistic context that became the foundation for interpreting the Quran. The tafsir methods used by the Tabi'in were also diverse, including tafsir bi al-ma'ŝūr, tafsir bi ar-ra'yi, tafsir bi al-ma'ānī, dan tafsir bi al-hadīŝ. Each method has its own strengths and weaknesses, but all are used to understand the meanings and messages contained in the Quran. Overall, the era of the Tabi'in was a crucial period in the development of Quranic exegesis. Tabi'in figures made important contributions to understanding the meanings and messages of the Quran, as well as introducing various tafsir methods that are still used today. Therefore, the study of the era of the Tabi'in in the context of Quranic exegesis is still a relevant topic today. Using the research library, we conducted this study to find out how much the contribution of the tabi'in period to the interpretation of the Quran.